EFEKTIVITAS METODE THINK PAIR SHARE TERHADAP MINAT DAN HASIL BELAJAR SISWA - Ahmad Masduki (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2020)
The purpose of this study was to determine the increase in interest and student learning outcomes of class XI OTKP-1 SMK YPE Nusantara Slawi Academic Year 2019/2020 in the subject of Islamic Religious Education (PAI) using a Think Pair Share (TPS) type cooperative approach. The research method uses a classroom action research method with two cycles. Each cycle involved 26 students who were divided into six groups. Each cycle consists of four stages, namely planning, implementing the action, observing, and reflecting. Data analysis used comparative descriptions of initial conditions, cycle I, and cycle II for interest variables in learning and learning outcomes. The results showed that applying the TPS-type cooperative learning model could increase student interest in learning and learning outcomes. Increased interest in learning in the first cycle of the first meeting reached 52%, and the second meeting reached 63%. The first meeting reached 76.66% in the second cycle, and the second meeting reached 88.33%. Learning outcomes increased from 34.61% to 80.77% in cycle I and 65.39% in cycle II.Keywords: Think Pair Share, Interest in Learning, Learning Outcomes